2018
DOI: 10.1002/jmri.25976
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive assessment of intracranial elastance and pressure in spontaneous intracranial hypotension by MRI

Abstract: 2 Technical Efficacy: Stage 3 J. Magn. Reson. Imaging 2018;47:1255-1263.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…Finally, the phase contrast magnetic resonance imaging (PC‐MRI) is a non‐invasive MRI sequence able to quantify variations in CSF flow. Three comparative studies confirmed abnormal results of PC‐MRI in SIH . These results were correlated to the CSF opening pressure in a case‐control study …”
Section: Discussionsupporting
confidence: 56%
“…Finally, the phase contrast magnetic resonance imaging (PC‐MRI) is a non‐invasive MRI sequence able to quantify variations in CSF flow. Three comparative studies confirmed abnormal results of PC‐MRI in SIH . These results were correlated to the CSF opening pressure in a case‐control study …”
Section: Discussionsupporting
confidence: 56%
“…Multiple successful smaller‐scale studies will therefore strengthen the justification and help obtain resources for a larger‐scale study. This work adds to multiple reports, some by independent investigators, which presented direct or indirect evidence supporting the validity of MR‐ICP. For example, Muehlmann et al demonstrated a good correlation between MR‐ICP and shunt opening pressure setting .…”
supporting
confidence: 64%
“…Significant correlation over a narrow range of ICP values was found when MR‐ICP was compared with ventriculo‐peritoneal shunt‐valve opening pressure in 15 children with hydrocephalus . A diagnostic accuracy of MR‐ICP was reported in idiopathic normal‐pressure hydrocephalus, pediatric idiopathic intracranial hypertension patients, subjects who acquired symptoms of mountain sickness using normobaric hypoxia, Chiari malformation type I patients, and in the early diagnosis of spontaneous intracranial hypotension …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Few studies have investigated CSF flow in patients with SIH focusing on CSF flow through the aqueduct. [32][33][34][35] One study reported lower CSF flow at C2/C3 among 23 patients with definite SIH and 4 patients with assumed SIH (controls: 1.2 ± 0.3 mL/s, patients: 0.8 ± 0.4 mL/s, p > 0.001). This is in contrast to current results.…”
Section: Discussionmentioning
confidence: 99%